Quelle sémantique pour les implicites ? - Kohei Kida (Corela)
The purpose of this article is to argue that some elements of meaning communicated by an utterance, which are most often seen in ordinary Truth-conditional semantics as implicit, can be reanalyzed in an argumentation-based semantics, the Theory of Semantic Blocks, as part of the explicit content of the utterance, insofar as such elements constitute semantically indecomposable "argumentative sequences".